THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE ON FIRM VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Amanda Ragellia Putri; Duwi Rahayu (Research Parks Publishers, 2026)
This study aims to analyze the influence of Corporate Social Responsibility and financial performance on firm value, with Good Corporate Governance serving as a moderating variable. The study employs a quantitative method using secondary data from energy sector companies listed on the Indonesia Stock Exchange for the period 2021– 2024. The research sample was obtained through purposive sampling, comprising 75 data after outlier removal. Data analysis was conducted using multiple linear regression with SPSS software. The results indicate that CSR does not affect firm value, whereas financial performance has a negative effect on firm value. The Board of Directors moderates the effect of CSR positively and that of financial performance negatively on firm value. The Independent Board of Commissioners moderates the negative influence of CSR and the positive influence of financial performance, while the Audit Committee is unable to moderate the influence of CSR but is able to moderate the influence of financial performance on firm value. This study is expected to serve as a reference for companies and investors in understanding the factors that influence firm value.